Evaluation of facial soft tissue asymmetric changes in Class III patients after orthognathic surgery using three-dimensional stereophotogrammetry. Issue 3 (March 2023) - Nike, E.; Radzins, O.; Pirttiniemi, P.; Vuollo, V.; Slaidina, A.; Abeltins, A.
Abstract: The aim of this study was to investigate changes in facial soft tissue asymmetry over time after orthognathic surgery in Class III patients using three-dimensional stereophotogrammetry. The study included 101 patients with a skeletal Class III malocclusion (72 female, 29 male; age range 19–53 years, mean age 28.6 years) who underwent orthognathic surgery. The minimum follow-up was 12 months. Three-dimensional photographs were acquired using the 3dMDtrio stereophotogrammetry system, and 21 anthropometric landmark positions were evaluated at three time points: before surgery (T0), 6 months (T1) and 12 months (T2) after surgery. Facial asymmetry was assessed and classified as follows: 0–2 mm, mild; 2–5 mm, moderate;> 5 mm, severe. The average distance for whole face asymmetry differed between T0 (median 0.76 mm) and T1 (median 0.70 mm); however, there was no statistically significant difference at any time point. The chin volume asymmetry score differed significantly between T0 (median 1.11 mm) and T1 and T2 (median 1.08 mm for both; P  < 0.001 and P  = 0.001, respectively), but not between T1 and T2 ( P  = 0.061). The study findings indicate that the asymmetry of the facial soft tissues has the potential to return after 6 months, without reaching the baseline.